(untitled) - Micietova, Maria; Sulgan, Marian (Doprava a spoje, 2011)
The article focused on the role of reverse logistics in the logistics system. It defines reverse logistics and green logistics and closes to present-day its application and importance. Describes its activities, characterizes the return products and mentioned the possibility of treatment with such products. This article also discusses the use of returnable plastic packaging in the automotive industry as one option for reducing adverse effects of reverse logistics.